The legality of a living trust as an instrument for Islamic wealth management: a Malaysian perspective - Halim, Akmal Hidayah (IIUM, 2011)
At present, the use of living trust is advocated as one of the best mechanisms to be considered for Islamic wealth management in Malaysia. Whilst the purpose of creating a living trust is to benefit the beneficiary, the settlor retains complete control and enjoyment over the trust property during his lifetime, and the beneficiary will only benefit the trust property after the death of the settlor. This instrument has been legally recognised to be applicable to Muslims in Malaysia and is enforceable against the settlor or his estate, irrespective of whether or not possession of the property was given to the beneficiary during the lifetime to the settlor or whether or not the settlor enjoyed the property during his lifetime. This situation is inconsistent with the rule of Islamic law on gift (hibah) and succession, especially when the beneficiary is a person who has the legal capacity to own property and who may be one of the legal heirs of the deceased-settlor. This article seeks to examine the execution of living trust by Muslims in Malaysia so that the rights of the beneficiaries under such trust are legally ascertained according to the Islamic law.